Lactational Weight Loss Of Sows Reared Under Field Condition Of Aizawl - Lalremruata, C.; Hmar, L.; Sharma, K.; Rosangzuali (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
The loss of body weight by sow during the period of lactation i.e from the day of farrowing till the day of weaning is considered as lactational weight loss. Thaker and Bilkei (2005) have reported that as weight loss of sows during lactation increases subsequent reproduction performance decreases. Most studies have also indicated that the lactational body weight loss varies depending upon the length of lactation, litter size and breed of sow etc. Therefore the present study was under taken to find out the lactational weight loss in the field condition so that measures can be taken for the improvement of the reproductive performance of sows.